Inventario forestal para la identificación de especies maderables del bosque de la estación experimental central de la Amazonía INIAP, cantón Joya de los Sacha, provincia de Orellana, periodo 2014 - Tipanluisa, Daniel (2014)
This research work was performed in San Carlo Sector, San Carlos Town, Joya de Sacha Canton, Orellana Province in the Amazon Region. It is located West Longitude, 282 meters altitude, UTM 291394, 9962429 coordinates. It belongs the Amazon Rainforest. The inventory purpose is on wood species which it is found in INIAP (EECA) Forest Station. The aim is to preserve and produce seeds in the future that focuses on sustainability in the Amazon of wood species. They are endangered. The forest inventory of wood species was made in an area of 23.52 hectares in the transept of linear and zigzag strips. The data were obtained in a field work. The results revealed that wood species inventoried have a diameter greater than 25cm….